The sociology of job training - Bills, David B., 1953- (Research in the sociology of work ;, 2003)
How workers learn how to do their jobs is central to an understanding of the changing nature of work in post-industrial society. The role of job or worker training has, however, been underdeveloped in sociological theories of work and the labor market. By most accounts, the ongoing penetration of information technology into the workplace, a transformed socioeconomic lifecourse, managerial preferences for high performance organizations, and the globalization of labour markets have collectively rendered traditional models of skill acquisition badly outmoded. This volume offers sophisticated sociological analyses of job training that go well beyond standard accounts of general versus specific skills and overly simple assumptions about employer and worker behaviour. The chapters examine such topics as the incentives available to employers to provide training, socially structured inequalities in access to training, and cross-societal differences in training institutions. They break new ground in investigating the content of job training as well as its incidence and duration. The contributors to the volume bring to bear both qualitative case study and quantitative research to explore the emerging role of training in post-industrial labor markets.